Liturgical Gift or Theological Burden? Teenagers and Ecumenical Liturgical Exchange Events - Nelson Robert Cowan; Emily Snider Andrews (Religions)
Assumptions about the preferences of teenagers in corporate worship regarding format, style, musical selections, and other experiences abound. Recognizing that teenagers are far from homogenous, we sought to listen deeply to how they process and define their experiences of worship, particularly through the lens of encountering liturgical difference. Our research team spent one week with approximately 35 highly religious, majority-Evangelical teenagers at Animate 2023 in Birmingham, Alabama—a summer camp with an emphasis in worship and the arts. Based on data from individual interviews and focus groups, this paper articulates some of our findings—namely that these highly devoted teenage worshipers demonstrate liturgical curiosity, delight in their own agency, and often desire to adopt practices that are foreign to them, even when some of those elements are deemed “weird”. The lived experiences of young people are often missing from conversations about their liturgical practices in both the Church and academy. While this study is not generalizable, it offers a micro glimpse into one worship arts camp, aiming to provide tangible data points to address this lacuna.